The weird world of cross-cultural false-belief research: a true- and false-belief study among Samoan children based on commands - Mayer, Andreas Frank; Träuble, Birgit (Journal of cognition and development, 2015)
Previous cross-cultural research using false-belief tasks has explored whether children's theory of mind develops synchronously across cultures. Success on false-belief tasks is usually interpreted as an important indicator of children's mental state understanding, but inconsistent findings have led to questions regarding the interpretation of children's success and failure. Based on the assumptions of perceptual access reasoning (Hedger & Fabricius, 2011) and reflecting on inconsistencies in cross-cultural false-belief research, we argue for the advantages of the additional use of true-belief tasks, which can help to differentiate between different levels of children's reasoning. Consequently, a false-belief task and a true-belief task were derived from typical Samoan adult-child interactions. The performance of 40 Samoan children aged 5 to 7 years old was compared to the performance of 40 age-matched German children. While German children passed both tasks, Samoan children failed the false-belief task and did not reply above chance level in the true-belief task. According to our knowledge, this is the first study using both a false-belief task and true-belief task in a cross-cultural setting. Our results reveal additional patterns of reasoning that are neither in line with perceptual access reasoning nor with a representational understanding of false beliefs. The study is discussed in terms of a more general problem of experimental research in non-Western settings.
Gesehen am 09.06.2020